ASSESSING THE STRATA HOUSING ATTRIBUTES FOR ELDERLY TO AGE IN PLACE IN KLANG VALLEY - Azmi, Amalina; Aning, Peter; Wan Abd Aziz, Wan Nor Azriyati; Juhari, Nur Hafizah; Khair, Nurhayati; Mentaza Khan, Puteri Ameera; Sivanathan, Sheelah (PLANNING MALAYSIA, 2021)
As the elderly population is burgeoning globally, the number of elderlies in Malaysia has also increased tremendously. Malaysia is expected to become an aging nation by 2030. The elderly in Malaysia prefer to age in place. At the same time, the trend of residing in landed property has shifted to strata housing due to several factors. Therefore, the purpose of this study is to assess the strata housing attributes for the elderly to age in place in Klang Valley. The list of housing attributes is divided into three categories: housing features, housing environment and technology. These attributive patterns emerge from various sources of literature reviews. Eight experts were identified and selected to validate the content based on their background as well as their area of specialization.